The Nomogram of Penile Length and Circumference in Iranian Term and Preterm Neonates - Soheilipour, Fahimeh; Rohani, Farzaneh; Dehkordi, Elham Hashemi; Isa Tafreshi, Roya; Mohagheghi, Parisa; Zaheriani, Seyed-Mohammadsalar; Jesmi, Fatemeh; Salehiniya, Hamid (Frontiers in Endocrinology, 2018)
Background and objectives: The normal length of penis in preterm and term neonates are different among different nations, and is affected by various factors. The present study aimed to determine stretched penile length (SPL) values and cutoff level of micropenis in term and preterm Iranian neonates, for the first time. Materials and methods: All male neonates born in two general hospitals of Tehran (Akbarabadi, and Rasoul hospitals), center of Iran, with gestational age of 28-42 weeks were included and their SPL and penile circumference (PC) were examinedon the first three days after birth by the same physician. Birth weight (BW), and height, gestational age, type of delivery, mother’s age, twin/multiple pregnancy, drug and medical history of mother during pregnancywere recorded and cutoff levels of two variables were calculated based on the collected variables for different gestational ages. Results: Among a total of 587 neonates, 203 neonates were born term and 384 preterm. Mean ±SD of neonates’ BW were 2682.51±739.30 (850-4800) gr. Mean ± SD of their SPL was 22.48±3.34 mm; 25.92±1.54 mm in term and 20.66±2.50 mm in preterm infants (P=0.001). Mean ± SD of penile circumference was 6.71±1.31 mm; 8.14±0.48 in term and 5.96±0.92 in preterm infants (P=0.001). SPL and PC were significantly correlated with type of delivery, number of parity, gestational age, BW, and crown-heel length, head circumference (P<0.001). Conclusion: This study suggested the first smoothed percentile values (±1, 2, and 3SD) of stretched penile length correlated with gestational age that can be used as a reference for Iranian newborns.